Constructing Nineteenth-Century Religion Literary, Historical, and Religious Studies in Dialogue - King, Joshua; Werner, Winter Jade (The Ohio State University Press, 2019)
Examines the ways in which religion was constructed as a category and region of experience in nineteenth-century literature and culture.